Computerized records: use in troubleshooting reproductive problems of commercial swine herds - Gary Dial (Kansas Agricultural Experiment Station Research Reports, 1990)
Swine production has become, in a relatively short time, one of the most competitive agribusinesses. The increase in international exportation of pork, dynamic changes in the efficiency of hog production, and the increasing preference of consumers for alternative meats has mandated that the swine industry be competitive with other producers of protein foodstuffs. Recent changes in the American swine industry have been dynamic. During the past 10 years, the financial advantage of volume selling and buying has led to an unwavering, irreversible evolution toward increasingly larger herd sizes. Accompanying this has been an ongoing trend toward decentralization away from the traditional grain-rich regions of the Midwest and consolidation of the meat packing industry. Although America remains one of the largest international producers of pork, imports into the domestic market have increased dramatically in recent years and now constitute approximately 8 percent of all pork consumed. In this climate of increased competition for more discerning markets, the independent producer has been faced with the challenge of either becoming efficient in the next decade or running the risk of no longer being competitive and no longer having a product desired by the marketplace. So, why keep records? A necessary prelude to being competitive in hog production is a usable record system allowing the producer to monitor both biological and financial performance and to troubleshoot production and financial problems.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Records; Analysis; Evaluation